Critical Analysis of the Tools of Achieving Truth in the Philosophy of Science - Nur Fatimatul Zahra; Rizqi Syahrur Ramadhan; Tamsik Udin (Penerbit Hellow Pustaka, 2026)
This paper examines the Critical Analysis of the Tools for Achieving Truth in the Philosophy of Science. The search for truth in the realm of science is not a linear journey relying on a single tool, but rather a complex and dynamic dialectical process. From the discussion that has been conducted, several main conclusions can be drawn. First, Rationalism and Empiricism are two fundamental epistemological pillars that, although seemingly contradictory, both make invaluable contributions. Second, Karl Popper's idea of ​​Falsification marks a crucial leap in our understanding of scientific truth. Third, the thoughts of post-Popper philosophers such as Thomas Kuhn and Imre Lakatos enrich and nuance the picture. Fourth, this picture is made more complete by recognizing the existence of radical perspectives and informal